DesignDirect : how to start your own micro brand - Ball, Roger; Overhill, Heidi (PTeC, 2012)
Mass production is no longer the only game in town. Small bands of visionary designers in Hong Kong, Shenzhen, and home offices around the world have bypassed corporate clients to reach consumers directly through the Internet. Outsourcing their production directly to low-cost Asian and digital suppliers, they are realizing the creative potential possible with personal control of your own micro-brand. Drawing on his experience as a designer and educator living at the crossroads of East and West, Roger Ball, with his colleague, Heidi Overhill, brings you a vision of the myriad opportunities waiting for designers and entrepreneurs as they step forward into the new era of DesignDirect. -- Zadní s. obálky
Keywords: marketing -- Čína -- Hongkong (Čína); internetový marketing -- Čína -- Hongkong (Čína); designéři -- Čína -- Hongkong (Čína); užitkový design -- Čína -- Hongkong (Čína); malé a střední podnikání -- Čína -- Hongkong (Čína); marketing -- China -- Hong Kong (China); Internet marketing -- China -- Hong Kong (China); designers -- China -- Hong Kong (China); design for use -- China -- Hong Kong (China); small and medium-sized business -- China -- Hong Kong (China); příručky; handbooks, manuals, etc